Endogenous WNT Signals Mediate BMP-Induced and Spontaneous Differentiation of Epiblast Stem Cells and Human Embryonic Stem Cells - Dorota Kurek; Alex Neagu; Melodi Tastemel; Nesrin Tüysüz; Johannes Lehmann; Harmen J.G. van de Werken; Sjaak Philipsen; Reinier van der Linden; Alex Maas; Wilfred F.J. van IJcken; Micha Drukker; Derk ten Berge (Stem Cell Reports, 2015)
Summary: Therapeutic application of human embryonic stem cells (hESCs) requires precise control over their differentiation. However, spontaneous differentiation is prevalent, and growth factors induce multiple cell types; e.g., the mesoderm inducer BMP4 generates both mesoderm and trophoblast. Here we identify endogenous WNT signals as BMP targets that are required and sufficient for mesoderm induction, while trophoblast induction is WNT independent, enabling the exclusive differentiation toward either lineage. Furthermore, endogenous WNT signals induce loss of pluripotency in hESCs and their murine counterparts, epiblast stem cells (EpiSCs). WNT inhibition obviates the need to manually remove differentiated cells to maintain cultures and improves the efficiency of directed differentiation. In EpiSCs, WNT inhibition stabilizes a pregastrula epiblast state with novel characteristics, including the ability to contribute to blastocyst chimeras. Our findings show that endogenous WNT signals function as hidden mediators of growth factor-induced differentiation and play critical roles in the self-renewal of hESCs and EpiSCs. : ten Berge and colleagues show that BMP signals direct the differentiation of human and mouse pluripotent cells via the induction of endogenous WNT signals. These determine trophoblast or primitive streak lineage specification. Furthermore, inhibition of endogenous WNT signals prevents spontaneous differentiation in both hESCs and mouse epiblast stem cells (EpiSCs) and maintains EpiSCs in a pregastrula, chimera-competent state.